Benzoxazine modified diglycidyl ether of bisphenol-a/silicon/siliconized epoxy hybrid polymer matrices: Mechanical, thermal, electrical and morphological properties. Issue 1 (2nd January 2019) - Karikal Chozhan, C.; Chandramohan, A.; Alagar, M.
Abstract: Benzoxazines modified epoxy hybrid polymer matrices were developed using benzoxazines (CBDDM and BMPBDDM ) and epoxy resins (DGEBA, SE and EP-HTPDMS) to make them suitable for high performance applications. The benzoxazine-epoxy hybrid polymer matrices were prepared via in-situ polymerization and were investigated for their thermal, thermo-mechanical, mechanical, electrical and morphological properties. Two types of skeletal modified benzoxazines namely 1, 1-bis(3-methyl-4-hydroxyphenyl)cyclohexane benzoxazine (CBDDM ) and bis(4-maleimidophenyl) benzoxazine (BMPBDDM ) were synthesized by reacting paraformaldehyde and 4, 4′-diaminodiphenylmethane with 1, 1-bis (3-methyl-4-hydroxyphenyl)cyclohexane and N -(4-hydroxyphenyl)maleimide respectively. Epoxy resins viz., diglycidyl ether of bisphenol-A (DGEBA), silicon incorporated epoxy (SE) and siliconized epoxy resin (EP-HTPDMS) were modified with 5, 10 and 15 wt% of benzoxazines using 4, 4′-diaminodiphenylmethane as a curing agent at appropriate conditions. The chemical reaction of benzoxazines with the epoxy resin was carried out thermally and the resulting product was analyzed by FT-IR spectra. The glass transition temperature, curing behavior, thermal stability, char yield and flame resistance of the hybrid polymers were analysed by means of DSC, TGA and DMA. Mechanical properties were studied as per ASTM standards. The benzoxazines modified epoxy resin systems exhibited lower values of dielectric constant and dielectric loss with an enhanced values of of arc resistance, glass transition temperatures, degradation temperatures, thermal stability, char yield, storage modulus, tensile strength, flexural strength and impact strength.